Edukacja literacka cudzoziemców w sytuacji przemian - Cudak, Romuald (Postscriptum Polonistyczne, 2020)
The article presents the most important changes in the contemporary literary criticism and the ways in which they influence thinking of Polish education among foreigners. The author concentrates above all on teaching Polish literature and culture; he begins with reflection on the very essence and aim of teaching Polish literature to foreigners, then he discusses the main problems and doubts that an educator nowadays must face. He describes also different possible models of Polish literary and cultural education designed for foreigners.